А CONTINENT THAT THINKS: POLITICAL THOUGHT IN SUB-SAHARAN AFRICA - Radanović, Srđan (Politeia, 2026)
Book Review: Danilo Babić, Political Thought in Sub-Saharan Africa: From Liberation to the Present. Belgrade: Institute of International Politics and Economics, 2026.